2021
DOI: 10.1002/essoar.10508224.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-Temperature Equation of State of FeH: Implications for Hydrogen in Earth's Inner Core

Abstract: We obtained the P-V-T equation of state of FeH based on volume measurements up to 142 GPa and 3660 K using a diamond-anvil cell • ΔV H , the volume increase of Fe by H atom, was determined as functions of P and T, enabling estimates of the H content in non-magnetic FeHx • We estimate the maximum H content in the inner core and discuss the possible compositional range of the Fe-H-Si-S inner core

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 30 publications
5
27
2
Order By: Relevance
“…(2022) showed that fcc FeH becomes less compressible above 41 GPa at room temperature, supporting the magnetic transition to non‐magnetic. We confirmed each time at 300 K before and after melting the sample that the unit‐cell volumes of the sample, including those of crystals that formed upon quenching temperature, were consistent with the compression curve of stoichiometric FeH (Tagawa et al., 2022).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…(2022) showed that fcc FeH becomes less compressible above 41 GPa at room temperature, supporting the magnetic transition to non‐magnetic. We confirmed each time at 300 K before and after melting the sample that the unit‐cell volumes of the sample, including those of crystals that formed upon quenching temperature, were consistent with the compression curve of stoichiometric FeH (Tagawa et al., 2022).…”
Section: Resultsmentioning
confidence: 84%
“…The melting curve of FeH was obtained by fitting the thermodynamic model to these not‐melting and melting data along with those previously reported below 20 GPa (Sakamaki et al., 2009) (Figure 1). Its d T /d P slope becomes substantially larger due to the loss of magnetism above ∼40 GPa (Tagawa et al., 2022). The melting point of non‐magnetic FeH is higher than the eutectic melting temperature of FeH x (1 < x < 2) observed between 43 and 127 GPa (Hirose et al., 2019) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Si concentration in the Fe-FeSi eutectic liquid has been shown to decrease from 11.5 wt% at 50 GPa to 8 wt% at 330 GPa 22 . On the other hand, the Fe-FeH eutectic composition (Fe + 0.8 wt% H) at ~50 GPa would remain similar at higher pressures because the temperature/pressure slope of the melting curve of stoichiometric FeH is comparable to that of Fe at >40 GPa 53 . The outer core composition should be within the liquidus field of Fe-the (Si, H)-depleted hcp phase-at 330 GPa (blue area in Fig.…”
Section: Discussionmentioning
confidence: 99%